The Investigation of Strata Control for Ultrasoft Coal Seam Mining. (16th April 2022) - Zhu, Chuanqi; Wang, Lei; Li, Shaobo
Abstract : Strata control of ultrasoft coal seam has been a critical problem for mining and geotechnical engineers in years. In this paper, the No. 66207 longwall panel at Xinzhuangzi coal mine, Anhui, China, was used as an example for study. A systematic approach using laboratory testing, numerical simulation, and field validation was implemented to investigate the influences of roadway layout and presplit blasting on mechanical properties of surrounding rock. Based on the results, an inward-stagger roadway layout with presplit blasting on roof was proposed for the regional strata control. The investigation on the relationship between angle of repose of ultrasoft coal and water content showed that the angle of repose first increased then decreased with increasing water content. The peak value was observed at 17.659% water content, suggesting water injection into ultrasoft coal seam can improve the coal mechanical properties and rib stability. The "high resistance, integral beam, two-stage rib+roof support system" was design to replace the traditional equipment, which can support the ultrasoft coal seam. The combination of this system and proposed "difference stepping" mining technique was capable of preventing roof and rib from failure, as well as mitigating the rockfall during moving hydraulic support. Based on the field validation, it was found that the stress concentration coefficient was relatively low during mining process. This was able to effectively manage the mining-induced stress while improving the productivity three times than without the technique. There was also no failure event observed during mining, such that the safety of mine workers was improved significantly.